The Prognostic Value of Troponin in Pediatric Polytrauma - Braun, Christian Karl; Schaffer, Annika; Weber, Birte; Huber-Lang, Markus; Kalbitz, Miriam; Preßmar, Jochen (Frontiers in Pediatrics, 2019)
Introduction: Severe trauma accounts for a great number of deaths among children and adolescents. The diagnostic value of troponin serum levels of severely injured patients has been reported for adults, but data on pediatric polytrauma (PT) are scarce. Therefore, we conducted a retrospective monocentered study analyzing the prognostic value of troponin T (TnT) in pediatric trauma patients at the time point of hospital admission. Methods: Data of 88 polytraumatized pediatric patients admitted to the emergency room of the University Hospital of Ulm, Germany, between 2007 and 2016 were analyzed retrospectively. The data source was the written and digital patient records. Interleukin-6 (IL-6), creatine kinase activity (CK activity), and lactate and TnT levels were measured by a certified clinical diagnostic laboratory; and patients were stratified for the Injury Severity Score (ISS). The prognostic value for lung contusion, organ dysfunction, and fatal outcome was statistically explored. The study was approved by the independent ethical committee of the University of Ulm (#44/18). Results: TnT levels were significantly increased in patients after severe PT compared with mild or moderate trauma severity as assessed by ISS values. Patients with TnT levels above the cutoff showed significantly increased levels of IL-6 and CK activity and a significantly prolonged stay in the intensive care unit. However, TnT levels did not correlate with absolute ISS values. TnT levels were significantly increased in patients with chest trauma and lung contusion. The incidence of lung contusion was associated with elevation of TnT. So was the onset of organ dysfunction, defined as a Sequential Organ Failure Assessment (SOFA) score ≥ 2 and fatal outcome, with a significant enhancement of plasma levels in children with organ dysfunction and in non-survivors. Conclusion: These descriptive data suggest that evaluation of TnT on admission of multiply injured children may help in predicting severity of injury and mortality in the clinical course after trauma and thus may be a useful addition to established prognostic parameters in the future.